Hydralazine targets cAMP-dependent protein kinase leading to sirtuin1/5 activation and lifespan extension in C. elegans - Esmaeil Dehghan (Nature Portfolio, 2019)
Hydralazine is a drug used in the treatment of heart failure and cancer, and it has recently been shown to promote lifespan in C. elegans. Here, the authors elucidate the mechanism of action of hydralazine, and show that it targets PKA to promote mitochondrial function via Sirtuin1/5.